Calotropis procera Latex Extract Affords Protection against Inflammation and Oxidative Stress in Freund's Complete Adjuvant-Induced Monoarthritis in Rats. (19th March 2007) - Kumar Kumar, Vijay L. Vijay L.; Roy Roy, Sanjeev Sanjeev
Abstract : In view of the well-established anti-inflammatory properties of latex of Calotropis procera (DL), the present study was carried out to evaluate the protective effect of its methanol extract (MeDL) against inflammation and oxidative stress in monoarthritis induced by Freund's complete adjuvant (FCA) in rats. Intra-articular injection of FCA produced inflammation of the joint with a peak effect occurring on day 4 where a maximum increase in the levels of myeloperoxidase and inflammatory mediators likePGE 2, TNF-α, and nitric oxide was observed. This was associated with oxidative stress with a marked reduction in the levels of glutathione, catalase, superoxide dismutase and glutathione peroxidase and an increase in the lipid peroxidation as indicated by the higher levels of thiobarbituric acid reactive substances (TBARSs). Subsequently on day 28 the histological analysis of the joint also revealed arthritic changes. Daily treatment of rats with MeDL (50 and 500 mg/kg) and standard anti-inflammatory drug rofecoxib (20 and 100 mg/kg), produced a significant attenuation in the inflammatory response and ameliorated the arthritic changes in the joint. The protection afforded by MeDL and rofecoxib was more pronounced than that of phenylbutazone and was associated with normalization of the levels of inflammatory mediators and biochemical parameters of oxidative stress. However, the overall protection afforded by rofecoxib was better than that of MeDL.